2011
DOI: 10.1126/science.1209236
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Biology of Synaptic Plasticity

Abstract: Synaptic plasticity is the experience-dependent change in connectivity between neurons that is believed to underlie learning and memory. Here, we discuss the cellular and molecular processes that are altered when a neuron responds to external stimuli, and how these alterations lead to an increase or decrease in synaptic connectivity. Modification of synaptic components and changes in gene expression are necessary for many forms of plasticity. We focus on excitatory neurons in the mammalian hippocampus, one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
358
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(376 citation statements)
references
References 65 publications
3
358
1
3
Order By: Relevance
“…The ability to visualize newly synthesized proteomes in biological systems will greatly advance our understanding of complex cellular functions occurring in space and time (1)(2)(3)(4). Currently, this endeavor is mainly pursued by several distinct contrast mechanisms including fluorescence staining, autoradiography, and mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to visualize newly synthesized proteomes in biological systems will greatly advance our understanding of complex cellular functions occurring in space and time (1)(2)(3)(4). Currently, this endeavor is mainly pursued by several distinct contrast mechanisms including fluorescence staining, autoradiography, and mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Many intricate biological processes, such as cell growth, differentiation, diseases, and response to environmental stimuli, require protein synthesis and translational control (1). In particular, long-lasting forms of synaptic plasticity, such as those underlying long-term memory, require new protein synthesis in a space-and time-dependent manner (2)(3)(4). Therefore, direct visualization and quantification of newly synthesized proteins at a global level are indispensable to unraveling the spatial-temporal characteristics of the proteomes in live cells.…”
mentioning
confidence: 99%
“…At the cellular level, these modifications underpin synaptic plasticity (Citri and Malenka, 2008;Ho et al, 2011), and in the whole animal support learning and memory (Morris, 2006;Neves et al, 2008) and its response to the environment (Nithianantharajah and Hannan, 2006;Baroncelli et al, 2010). These changes involve both functional and structural adaptations in terms of intrinsic excitability (Davis, 2006), postsynaptic glutamate receptor complement (Kerchner and Nicoll, 2008;Kessels and Malinow, 2009), neurotransmitter release (Citri and Malenka, 2008), and in the shape and density of dendritic spines, axonal arbors, and synaptic boutons (Holtmaat and Svoboda, 2009;Hübener and Bonhoeffer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of synaptic plasticity is highly controlled by brain-derived neurotropic factor (BDNF) protein binding to specific tropomyosin receptor kinase B (TrkB) Electro-acupuncture ameliorates cognitive impairment via improvement of brain-derived neurotropic factor-mediated hippocampal synaptic plasticity in cerebral ischemia-reperfusion injured rats receptors (11,12). BDNF is a member of the neurotrophin family (13,14), which is known to not only promote the activity of nerve growth, but also to modulate synaptic plasticity (15). For instance, numerous studies have indicated that BDNF enhances hippocampal synaptic plasticity by inducing local protein synthesis in the pre-synaptic terminal and post-synaptic dendrites of rats with cerebral ischemic injury (16,17).…”
Section: Introductionmentioning
confidence: 99%